PENGARUH TINGKAT PENDIDIKAN ORANG TUA TERHADAP MOTIVASI BELAJAR SISWA DI MA MIFTAHUL HUDA - S. Andriyanto (UNISAN JURNAL, 2023)
Research with the title "The Effect of Parental Education Level on Student Learning Motivation at MA Miftahul Huda . Identification of the problem is 1) low student learning motivation. 2.) Parents pay less attention to children who are learning. 3.) Parents are busy with work. 4.) The educational level of parents tends to be low. To collect data relevant to this research, used the Questionnaire Method, Documentation Method, Observation Method, Interview Method. After the data is well collected, the next step is to process or analyze the data to prove or test the hypotheses that have been formulated, while the analytical method used in this study is Percentage, Chi Square Analysis Method. The results of the study show that there is an influence between the level of parental education and the learning motivation of MA Miftahul Huda students because the interpretation value is very strong, namely 22,084.